The Use of Wordwall.net as Learning Media to Enhance Vocabulary Mastery of Physical Education Students - Putra, Aziiz Rahman; Febrianti, Mariska; Pradana, Ami; Banat, Azizatul (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
Vocabulary mastery is a basic thing that must be mastered by someone in learning a language. Unfortunately, currently many EFL students still have difficulty mastering English vocabulary. One of the media that can be used by teachers to improve students' vocabulary mastery is word wall (Supraba, 2019). The objectives of this research are to analyze the use of wordwall.net media in teaching English vocabulary and also to identify the advantages and disadvantages of using wordwall.net according to the perceptions of English teachers in teaching English vocabulary to Physical Education students at Dehasen University Bengkulu. This research was field research with a descriptive qualitative method. The data was collected based on observations, interviews and documentations. The results of study showed that teaching vocabulary (with an emphasis on nouns) through word wall media can improve students' vocabulary, and researchers found the most effective method for teaching English vocabulary (with an emphasis on nouns and verbs) through word wall media. In addition, the use of wordwall.net is also considered effective in increasing the motivation and enthusiasm of Physical Education students in learning English by answering questions in turns so that they are challenged to compete with friends and not learn monotonously by sitting and listening on a bench. Meanwhile, the advantages of wordwall.net include various interesting features, automatic reporting of results, providing printable and easily accessible materials. On the other hand, its disadvantages include being prone to fraud because students can access links freely anytime and anywhere, they have the opportunity to work together or cheat on each other without the teacher's knowledge. In addition, both teacher and learner should know on how to use smartphone, PC, or Laptop in order to access and to operate the wordwall.net application.